DYNAMICS OF AFRICAN TRADITIONAL AND CULTURAL PRACTICE AS A SOCIAL CONTROL MECHANISM: A DETERRENT THEORETICAL ANALYSIS ON THE ALEKWU BELIEF SYSTEM AMONG THE IDOMA PEOPLE IN NIGERIA - Daniel, Rosemary Onchi (International Studies Journal)
Strong traditional and cultural convictions prevalent in many African communities place a premium on deference to established rules and refraining members from abominable or deviant behaviour. These ideas have the potential to exert strong social control by discouraging individuals from acting in an abnormal manner. Traditional and cultural customs in Africa have long been used as a form of social control mechanism which is known for regulating conduct and preserving community peace. The Alekwu belief system is one such tradition that is firmly ingrained in the Idoma community of Nigeria. In this paper, the Alekwu belief system of the Idoma people will be discussed, along with its strengths and weaknesses as a social control mechanism.A spirit-medium known as the Alekwu is thought to be able to connect with the afterlife. Alekwu is usually consulted for a number of purposes, such as giving advice on way forward on private problems, marital issues, diagnosing and treating illnesses, and settling arguments among relatives, couples and community members.The paper unveils how the Idoma traditional belief system affects their morals, attitudes, and actions as well as how it helps to preserve social order in their neighborhood. This paper is anchored on deterrence theory of punishment as a framework to analyze the Alekwu belief system's deterrent effects on behavior within the Idoma community and provide a theoretical analysis of the Alekwu belief system as a deterrent mechanism that influences social norms, values, and behavior among the Idoma people.